Kinesiophobia among health professionals’ interventions: a scoping review - Lilian Doutre; Maryse Beaumier; Andrée-Anne Parent; Sébastien Talbot; Mathieu Tremblay (PeerJ, 2024)
Health professionals are regularly confronted with patients suffering from a fear of movement-related pain (unknown as kinesiophobia). The fear-avoidance attitudes and beliefs of healthcare professionals are likely to play a key role in their patients’ therapeutic approach. However, kinesiophobia among health professionals is a relatively young topic. This scoping review aims to explore and catalogue the extent of scientific research that identifies the causes and consequences of kinesiophobia among health professionals while they perform their interventions. The review was based on the Joanna Briggs Institute manual and the PRISMA method for a scoping review. The research was conducted in May 2024 using CINHAL, Medline and Sportdiscus databases with the search terms “fear-avoidance”, ”kinesiophobia“, “pain-related” and “physical therapist”. Out of 2,162 potential studies, thirteen articles were included. No study directly mentioned kinesiophobia among health professionals, but it was studied through fear-avoidance beliefs. Two-thirds of the articles indicate that professionals with fear-avoidance beliefs tend to refer their patients to other specialists less frequently and limit their patients’ activity, despite treatment guidelines. Most of the studies found were physiotherapists’ interventions for chronic back pain patients. The current review emphasizes the need for additional studies involving more healthcare professionals and diverse health conditions.